Multimerization of the Drosophila zeste protein is required for efficient DNA binding. - Chen, J D (1993)
The Drosophila zeste protein forms multimeric species in vitro through its C-terminal domain. Multimerization is required for efficient binding to DNA containing multiple recognition sequences and increasing the number of binding sites stimulates binding in a cooperative manner. Mutants that can only form dimers still bind to a dimeric site, but with lower affinity. Mutations or progressive deletions from the C-terminal show that when even dimer formation is prevented, DNA-binding activity is lost. Surprisingly, binding activity is regained with larger deletions that leave only the DNA-binding domain. Additional protein sequences apparently inhibit DNA binding unless they permit multimerization. The DNA-binding domain peptides bind strongly even to isolated recognition sequences and they bind as monomers. The ability of various zeste peptides to stimulate white gene expression in vivo shows that multimeric forms are the functional species of the zeste product in vivo. The DNA-binding domain peptide binds well to DNA in vitro, but it cannot stimulate white gene expression in vivo. This failure may reflect the need for an activation domain or it may be caused by indiscriminate binding of this peptide to non-functional isolated sites. Multimerization increases binding specificity, selecting only sites with multiple recognition sequences.